OPTIMALISASI MICROBLOGGING TWITTER SEBAGAI ALAT KEHUMASAN DALAM PERUSAHAAN - Kirana Dwitia Putri; Irwansyah - (Jurnal Penelitian Komunikasi dan Opini Publik, 2018)
Every companies that run the business, they always focus on distributing products and services to all of their consumers in public. Companies, must be able to create strategies to broaden distribution action and awareness about the company itself. Customers, residing in the public have the right to understand a product or service that is, and without any doubt they have to be always able to obtain information about the company. In today's era, ideally it is no longer difficult to get any information with the help of internet. Similarly, the ideal company has been optimizing the use of the Internet as a performance tool. The author of this research, put forward the concept that can bridge the company with consumers through the relationship with using microblogging available on social media that is Twitter. Public Relations practitioners, can communicate further to conduct a communication campaign on the increasingly segmented consumer, thanks to Twitter and the delivery of information is now not limited space and time.Keywords : Microblogging, Twitter, Social Media, Public Relations, Communication